Stability and Instability of Solitary Waves for Abstract Complex Hamiltonian System (Journal of Partial Differential Equations, 2020)
This paper is concerned with the orbital stability and orbital instability of solitary waves for some complex Hamiltonian systems in abstract form. Under some assumptions on the spectra of the related operator and the decaying estimates of the semigroup, the sufficient conditions on orbital stability and instability are obtained.